Measuring decent work in self-managed cooperatives: the Costa Rica case - Vargas Montero, Maritza (2019)
Medición del trabajo decente en las cooperativas de autogestión: aplicación en Costa Rica   Costa Rica is a country with extensive experience in the development of cooperatives, which have occupied an important place in the development strategies of the country, generating a significant volume and diversity of initiatives. Historically, cooperatives have had an impact on human development through the generation of employment and reduction of poverty and inequality. On the other hand, the concept of decent work is an integral approach to work, so that promoting it also means changing the way the global economy works, so that its benefits reach more and more people. The objective of this article is the measurement of the variable of decent work in Costa Rican self-management cooperatives.